Characteristics of the indigenous microflora from five silage crops in 1987 - Hart, R.A.; Niroomand, F.; Bolsen, K.K.; Lubinski, M.A.; Aimutis, W.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Indigenous lactic acid bacteria (LAB) were isolated from five silage crops in the 1987 growing season: wheat, alfalfa, com, interseeded grain sorghum and soybeans, and forage sorghum. All crops had post-harvest LAB counts that exceeded 5 x 105 colony-forming units/g. There were no significant correlations between rate of fermentation during the first 7 d post-ensiling and the indigenous LAB counts. However, corn and sorghum, which fermented rapidly, had higher populations of homofermentative LAB, and the isolates showed higher rod to cocci ratios compared to the other three crops. Most of the homofermentative rods isolated were Lactobacillus plantarum, and most of those isolates had slow growth rates and narrow growth temperature ranges. A variety of heterofermentative lactobacilli were isolated from all five crops. Two unidentifiable Streptococcus species were isolated from wheat and alfalfa.
Keywords: Beef; Microflora; Silage; Lactic acid bacteria